A single-phase hybrid active power filter with photovoltaic application - Tan, Perng Cheng (2006)
The past several years have seen a rapid increase of power electronics-based loads connected to the distribution system. These types of loads draw nonsinusoidal current from the mains, degrading the power quality by causing harmonic distortion. This thesis proposes a single-phase hybrid active power filter with photovoltaic application. The proposed topology interconnects a passive high-pass filter in parallel with a shunt active power filter and a DC source that represents the photovoltaic array. The uniqueness of the proposed topology is the fact that it improves the harmonic filtering performance of a basic shunt active power filter, as well as simultaneously supplies the power from the photovoltaic array to the load. The compensation current reference for the proposed topology is obtained by using the extension instantaneous reactive-power theorem. This theorem simplifies the equations for the current reference estimation, thus leading to a more efficient implementation in digital signal processor. To generate the compensation current that follows the current reference, the fixed-band hysteresis current control method is adopted. This work describes the design of circuit topology, control system, highpass filter and compensation current reference estimation. The system is verified by simulation using MATLAB/Simulink simulation package. To validate the result, a 500 VA laboratory prototype is constructed. It is based on the dSPACE DS1104 digital signal processor. Experimental results show that the system effectively reduces the total harmonic distortion of the source current from 130.2 % to 19.6 %. Furthermore, it is demonstrated that the system can also supply active power to the load.